Dynamic Time-history Elastic Analysis of Steel Frames Using One Element per Member. (November 2016) - Liu, Si-Wei; Bai, Rui; Chan, Siu-Lai
Abstract: This paper proposes an efficient numerical simulation technique for dynamic time-history analysis of space steel frames by one-element-per-member model, considering geometric nonlinearity including P-Δ-δ effects, large global deflections and member deformations. The curved arbitrarily-located-hinge (ALH) beam-column element is employed for capturing members' behaviors and simulating initial imperfections, where the internal degree-of-freedoms (DOFs) are condensed for improving the computational efficiency. The consistent element mass matrix is derived based on the Hermite interpolation function, and the Rayleigh damping model is adopted for representing the system viscosity. To solve the equation of the time-history motion, a direct time-integration method via Newmark's algorithm is utilized for the step-by-step solution. A robust numerical procedure using the incremental secant stiffness method is introduced for the large deflection analysis of space frames, allowing arbitrary rotations in a three-dimensional space. Verification examples are given to validate the present model in handling dynamic behaviors of the steel frames and members under the transient actions. The distinct feature of the research is to propose an effective analytical framework using high-performance elements, dramatically improving the numerical efficiency and making the method being practical. Highlights: Dynamic time-history elastic analysis by one-element-per-member model is proposed. Geometric nonlinearity allowing large deflections and deformations are considered. The curved arbitrarily-located-hinge (ALH) beam-column element is employed. Direct time-integration method via Newmark's algorithm is utilized. A significant saving in the computational expense is achieved.